Psychometric Properties of the Brazilian 12-Item Short-Form Health Survey Version 2 (SF-12v2) - Damásio, Bruno Figueiredo; Andrade, Thiago Francisco; Koller, Sílvia Helena (Paidéia (Ribeirão Preto), 2015)
The 12-Item Short-Form Health Survey, in its initial (SF-12) and revised form (SF-12v2) is a widely used measure to evaluate health-related quality of life (HRQoL). The present study evaluates the factor structure and reliability of the Brazilian version of the SF-12v2. Participants were 627 subjects (74.1% women), aged from 18 to 88 years (M = 38.6; SD = 13.16), from 17 Brazilian states. Confirmatory factor analyses suggested two pairs of error terms to be highly correlated (3a-3b; and 4a-4b). A qualitative inspection showed an overlap of content among these items. The respecified model presented adequate fit indices. Convergent validity was also tested with measures of health-related self-care, subjective happiness, life satisfaction, depression and self-efficacy. Expected correlations were found between the SF-12v2 and these measures. Results showed initial evidence in favor of using the SF-12v2 as a measure of physical and mental health in the Brazilian context.